Best feature selection and data visualization for breast cancer prediction - Hemel, Tanjim Ahmed; Parvez, Rohan (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.